2014
DOI: 10.1097/pcc.0000000000000119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dexmedetomidine and Postoperative Pain Management in Patients With Adolescent Idiopathic Scoliosis

Abstract: There was no difference in opioid use related to dexmedetomidine on any postoperative day. The only variable showing a significant opioid sparing effect was the use of local anesthetic infusions via elastomeric pumps. Using continuous local anesthetic infusions instead of dexmedetomidine could eliminate the need for ICU admission, require shorter hospital stays, and reduce costs while still providing safe and effective pain control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 20 publications
3
14
0
4
Order By: Relevance
“…The analgesic and opioid-sparing effect of DEX have been well described in previous studies, both in adult and children. 7 , 20 , 21 Similar to the present data, these studies reported significantly lower VAS, morphine consumption, and morphine demands. Together with these findings, the present study indicated that intraoperative administration of DEX is a potential way to be used to promote morphine-based PCA after abdominal surgery.…”
Section: Discussionsupporting
confidence: 90%
“…The analgesic and opioid-sparing effect of DEX have been well described in previous studies, both in adult and children. 7 , 20 , 21 Similar to the present data, these studies reported significantly lower VAS, morphine consumption, and morphine demands. Together with these findings, the present study indicated that intraoperative administration of DEX is a potential way to be used to promote morphine-based PCA after abdominal surgery.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, patients from the PRD group who received intraoperative dexmedetomidine had lower pump-press number, and consumed less morphine than those in the PRS group. The analgesic and opioid-sparing effects of dexmedetomidine have been well described in previous studies both in adults and children 7 16 17 . Similar to the present data, these studies reported significantly lower VAS scores and morphine consumption and fewer morphine demands.…”
Section: Discussionsupporting
confidence: 54%
“…It also had a potential to reduce postoperative nausea and vomiting. Morphine-sparing effect of dexmedetomine have also been well established by other early studies both in adults and pediatric patients (McQueen-Shadfar et al, 2011; Gupta et al, 2013; Jones et al, 2014). Recent clinical studies also reported that dexmedetomidine could be used to control postoperative analgesia and chronic pain in breast cancer patients following radical hamstectomy (Jain et al, 2012; Mohamed et al, 2014; Mohta et al, 2016).…”
Section: Discussionmentioning
confidence: 60%